2016
DOI: 10.3382/ps/pew172
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive response of broilers to dietary phosphorus and calcium restrictions

Abstract: The aim of this study was to evaluate the capacity of chickens to adapt to and compensate for early dietary restriction of non-phytate P ( NPP: ) and/or Ca (10 to 21 d) in a later phase (22 to 35 d), and to determine whether compensatory processes depend on the P and Ca concentrations in the finisher diet. Four diets were formulated and fed to broilers from 10 to 21 d in order to generate birds with different mineral status: L (0.6% Ca, 0.30% NPP), L (0.6% Ca, 0.45% NPP), H (1.0% Ca, 0.30% NPP), and H (1.0% Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 27 publications
16
51
1
Order By: Relevance
“…The absence of growth performance alteration when reducing dietary Ca and nPP during days 22 to 37 is in agreement with the results of Wilkinson et al (2014), Delezie et al (2015) and Rousseau et al (2016) for BW gain and feed conversion ratio. A further reduction of Ca and nPP during the finisher phase increased the deficit in bone mineralisation, from −11% on day 21 (C v. L) to −20% on day 37 (CC v. LL) based on tibia ash content.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…The absence of growth performance alteration when reducing dietary Ca and nPP during days 22 to 37 is in agreement with the results of Wilkinson et al (2014), Delezie et al (2015) and Rousseau et al (2016) for BW gain and feed conversion ratio. A further reduction of Ca and nPP during the finisher phase increased the deficit in bone mineralisation, from −11% on day 21 (C v. L) to −20% on day 37 (CC v. LL) based on tibia ash content.…”
supporting
confidence: 90%
“…Faridi et al (2015) showed that in the absence of phytase or vitamin D 3 , dietary nPP should be above 3.5 g/kg during the first 21 days in order to maximise tibia ash content. As dietary depletion increased, Ca and nPP relative transfer increased suggesting an increase in apparent digestibility of Ca and phosphorus in the intestine as reported by Rousseau et al (2016) in chicks fed low-phosphorus or Ca diets for 10 days. Studies have suggested that depletion appears to stimulate the expression of mRNA encoding Ca transporters CALB1, SLC8A1 and ATP2B1 and phosphorus transporters SLC20A1 and SLC34A2 (Centeno et al, 2004;Bar, 2009;Proszkowiec-Weglarz and Angel, 2013) in the intestine and the kidney.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…The initial pH and the buffering capacity to pH 3 were measured according to Lawlor et al (2005). Dry matter of diets, feces and digestive content of ileum and cecum, and P, Ca and TiO 2 Rapeseed fiber and mineral digestibility analysis were performed as previously explained by Rousseau et al (2016). Phytase activity was measured according to Engelen et al (1994).…”
Section: Analysesmentioning
confidence: 99%